Algorithmic Foundations of Robotics X Proceedings of the Tenth Workshop on the Algorithmic Foundations of Robotics - Frazzoli, Emilio; Lozano-Perez, Tomas; Roy, Nicholas; Rus, Daniela; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Algorithms are a fundamental component of robotic systems. Robot algorithms process inputs from sensors that provide noisy and partial data, build geometric and physical models of the world, plan high-and low-level actions at different time horizons, and execute these actions on actuators with limited precision. The design and analysis of robot algorithms raise a unique combination of questions from many elds, including control theory, computational geometry and topology, geometrical and physical modeling, reasoning under uncertainty, probabilistic algorithms, game theory, and theoretical computer science. The Workshop on Algorithmic Foundations of Robotics (WAFR) is a single-track meeting of leading researchers in the eld of robot algorithms. Since its inception in 1994, WAFR has been held every other year, and has provided one of the premiere venues for the publication of some of the eld's most important and lasting contributions. This books contains the proceedings of the tenth WAFR, held on June 13{15 2012 at the Massachusetts Institute of Technology. The 37 papers included in this book cover a broad range of topics, from fundamental theoretical issues in robot motion planning, control, and perception, to novel applications.
From the Contents: The Minimum Constraint Removal Problem with Three Robotics Applications -- Hierarchical Decision Theoretic Planning for Navigation Among Movable Obstacles -- Robust complete path planning in the plane.
Keywords: Robotics; Automation; Artificial intelligence; Robotics and Automation; Artificial Intelligence